Consequences of Hyperoxia and the Toxicity of Oxygen in the Lung - William J. Mach; Amanda R. Thimmesch; J. Thomas Pierce; Janet D. Pierce (Nursing Research and Practice)
Oxygen (O2) is life essential but as a drug has a maximum positive biological benefit and accompanying toxicity effects. Oxygen is therapeutic for treatment of hypoxemia and hypoxia associated with many pathological processes. Pathophysiological processes are associated with increased levels of hyperoxia-induced reactive O2 species (ROS) which may readily react with surrounding biological tissues, damaging lipids, proteins, and nucleic acids. Protective antioxidant defenses can become overwhelmed with ROS leading to oxidative stress. Activated alveolar capillary endothelium is characterized by increased adhesiveness causing accumulation of cell populations such as neutrophils, which are a source of ROS. Increased levels of ROS cause hyperpermeability, coagulopathy, and collagen deposition as well as other irreversible changes occurring within the alveolar space. In hyperoxia, multiple signaling pathways determine the pulmonary cellular response: apoptosis, necrosis, or repair. Understanding the effects of O2 administration is important to prevent inadvertent alveolar damage caused by hyperoxia in patients requiring supplemental oxygenation.